MODERN PROBLEMS AND RATIONAL USE METHODS OF ARID SOILS IN AZERBAIJAN (AS AN EXAMPLE OF JEYRANCHOL) - İ. A. Guliev and M. Y. Khalilov and İ. İ. Mardanov (Scientific Journal of Pedagogy and Economics, 2019)
The problems in dynamical changes assessment occurring as a result of mutual impact of the available state, natural and antropoghenic factors in Azerbaijan arid soils have been paid attention, but the scientific groundings have been based on our perennial soil investigations in Jeyranchol at the global desertification problems context in the article.